Utilization of Calcium Carbide Residue and Bottom Ash as a Binder for Solid Load-bearing Concrete Block - ตรีผอง กมล; เจียมมีปรีชา วีรพันธุ์; อับดุลมาติน อรรคเดช (Srinakharinwirot University Engineering Journal, 2020)
The aim of this research is the use of calcium carbide residue and bottom ash as a binder in concrete block to reduce the Portland cement. In this study, the calcium carbide residue and bottom ash were ground and mixed in the ratio between calcium carbide residue to bottom ash of 30:70 by weight (CB) to use as a binder for casting solid load-bearing concrete block. The specimen size of the block use in this study is 100x100x200 mm3. The density, water absorption and compressive strength of CB concrete block were investigated and compared with concrete block with Portland cement as a binder (CT). This result found that the water absorption and compressive strength of concrete block depended on its density i.e., the high density of the block resulted in the decrease of water absorption and increase compressive strength. The use of CB binder for casting concrete block affected on higher water absorption and lower compressive strength than CT concrete block. However, the water absorption and compressive strength of CB concrete block could be improved by added 10% of Portland cement by weight, used the pressure of 6 ksc to cast the block and decreased the water to binder ratio in the mixture. Therefore, the water absorption and compressive strength of the improved CB concrete block could meet the requirement of solid load-bearing concrete block for using as the wall above and below ground level without protecting surface in accordance with TIS 60-2561.